Risk Factors Associated with Recurrence in Patients with Solid Pseudopapillary Tumors of the Pancreas - Serrano, Pablo E; Serra, Stefano; Al-Ali, Hassan; Gallinger, Steven; Greig, Paul D; McGilvray, Ian D; Moulton, Carol-Anne; Wei, Alice C; Cleary, Sean P (JOP. Journal of the Pancreas, 2014)
Context Solid pseudopapillary tumors (SPT) are rare, generally low grade pancreatic neoplasms that occasionally display malignant behavior. Objective To analyze the clinical and pathological features associated with increased risk of recurrence of SPT. Methods Cohort study of patients with SPT who underwent resection of the primary tumor and in selected cases resection of metastatic disease from 1999-2013 at a single tertiary care Hepatopancreatobiliary center. Risk factors for recurrence were statistically analyzed. Results There were 32 patients. The mean age was 35.65 years (standard deviation: 12.26), 26/32, 81.25% were female. Median size of resected tumors was 4.7cm (1.1-14.5). Most were solid and cystic (22/32, 68.75%), encapsulated (27/32, 84.4%) and located in the pancreatic body or tail (22/32, 68.75%). All displayed strong β-catenin, cyclin D1, CD56, and progesterone receptor staining with loss of E-cadherin. Most stained positive for vimentin (15/16, 93.75%) and CD10 (17/18, 94.4%). Median follow-up was 43 months (range: 3-207); 3/32, 9.38% recurred (all after 5-years from curative resection) and 1 died by the end of the study period, 11 years after diagnosis. Patients who developed recurrences (n=3) more commonly had synchronous metastases at presentation (P=0.006), lymphovascular invasion (P=0.04) and invasion of tumor capsule (P=0.08) compared to those who did not have disease recurrence. Conclusions Lymphovascular invasion, synchronous metastases and local invasion of tumor capsule are associated with aggressive behavior. Since recurrences may occur >5 years from resection, this high-risk group should undergo extended follow-up. Progression and recurrence is slow, therefore, resection of liver metastases can offer long-term survival. Image: Vimentin staining of SPT<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; display: inline !important; float: none; background-color: #ffffff;">.